If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b(b) = -3b Multiply b * b b2 = -3b Solving b2 = -3b Solving for variable 'b'. Reorder the terms: 3b + b2 = -3b + 3b Combine like terms: -3b + 3b = 0 3b + b2 = 0 Factor out the Greatest Common Factor (GCF), 'b'. b(3 + b) = 0Subproblem 1
Set the factor 'b' equal to zero and attempt to solve: Simplifying b = 0 Solving b = 0 Move all terms containing b to the left, all other terms to the right. Simplifying b = 0Subproblem 2
Set the factor '(3 + b)' equal to zero and attempt to solve: Simplifying 3 + b = 0 Solving 3 + b = 0 Move all terms containing b to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + b = 0 + -3 Combine like terms: 3 + -3 = 0 0 + b = 0 + -3 b = 0 + -3 Combine like terms: 0 + -3 = -3 b = -3 Simplifying b = -3Solution
b = {0, -3}
| x+32-24=45 | | 4x-3.72=60 | | 6y-9=14y+7 | | 7x-6=42-5x | | 100a=193748563646564646465646565656 | | 5a-3=5a+4 | | y=-12x-x+20 | | (-5)x(-8)(-9)= | | 6x^2+3=-102 | | 4x+12=-3x+-9 | | 432=36b | | y-84=10.25 | | X-123=77-9x | | 6x+7=8-15 | | (+5)+(+12)+(+17)= | | 9r^2+3=48 | | 436+w=600 | | 70=0.6r | | c^2+12c+36-q^2= | | F(x)x=2.4 | | z+48=136 | | 4x^6+6x^3-7= | | x^2-9+x^2-x=180 | | 4x+12=-3x-9 | | F(x)whenx=2.4 | | -4(8-2m)=-96 | | 4a-3[a-(2a+1)]= | | 2x-85=11x+167 | | x^2-0+45=0 | | A+6a-14=64 | | w^8+17w^4+70= | | 7x+2yz=-3x+1 |